Juan de Onate's Colony in the Wilderness an early history of the American Southwest - McGeagh, Robert (Santa Fe, N.M. : Sunstone Press, 1990)
A generation before the establishment of the European colonies on the East Coast of America, Spanish explorers and friars were trudging the deserts and mountains of the Southwest in search of souls, riches, and glory. By 1598, Juan de Onate had established the first permanent settlement in the American Southwest, twenty-two years before the Pilgrims founded Plymouth Colony. The story of this first colony, the explorations, the defeats and successes, the hopes blighted and the hopes fulfilled are told in this concise history of the era. Cover
Spine title: Colony in the wilderness.
Includes index.
73459
Keywords: Onate, Juan de, -- 1549?-1624.; Spaniards -- History -- New Mexico; New Mexico -- Discovery and exploration; New Mexico -- History -- To 1848